2014
DOI: 10.1016/j.ejmp.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A comparison among different techniques for human ERG signals processing and classification

Abstract: Feature detection in biomedical signals is crucial for deepening our knowledge about the involved physiological processes. To achieve this aim, many analytic approaches can be applied but only few are able to deal with signals whose time dependent features provide useful clinical information. Among the biomedical signals, the electroretinogram (ERG), that records the retinal response to a light flash, can improve our comprehension of the complex photoreceptoral activities. The present study is focused on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
12
0
3
Order By: Relevance
“…Review of the literature showed that several mother wavelets have been applied in DWT of the ERG response, such as the “Daubechies” wavelets [ 20 , 21 , 25 ], the “Haar” wavelet [ 24 , 35 ] and the “Mexican hat” [ 23 , 36 , 37 ]. For glaucoma, Miguel-Jiménez et al have successfully applied DWT to the global flash mfERG response in advanced glaucoma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the literature showed that several mother wavelets have been applied in DWT of the ERG response, such as the “Daubechies” wavelets [ 20 , 21 , 25 ], the “Haar” wavelet [ 24 , 35 ] and the “Mexican hat” [ 23 , 36 , 37 ]. For glaucoma, Miguel-Jiménez et al have successfully applied DWT to the global flash mfERG response in advanced glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used to analyze the photopic negative response in the full-field ERG of healthy subjects [ 22 ]. Barraco et al [ 23 ] compared different analytical approaches (including application of the continuous wavelet transform, CWT) to analyze the a -wave of the full-field ERG, demonstrating consistently altered photoreceptor behavior in various diseases. Nair and Joseph [ 24 ] could differentiate patients with congenital stationary night blindness, rod–cone dystrophy and central retinal occlusion from healthy controls using wavelet analysis of the full-field ERG.…”
Section: Introductionmentioning
confidence: 99%
“…The students had attended a previous focus session lasting 8 hr, covering the features of the ERG and the different techniques of data processing, such as the Fourier Transform, the Wavelet Analysis, the Principal Component Analysis, etc. . In particular, for improving and speeding up the clinical analysis and classification of the ERGs, during the regular lectures, a procedure based on the Empirical Mode Decomposition (EMD) coupled with an Artificial Neural Network (ANN), has been explicated to the students; this method turned out to be very effective and adequate for processing ophthalmologic data .…”
Section: Methodsmentioning
confidence: 99%
“…In clinical routine, the widespread method used to analyze the ERGs is based on the visual examination of the morphology of the waveforms. However, this analysis often fails to detect or to recognize an eventual pathology or its degree of seriousness; consequently, more sophisticated clinical ophthalmologic investigations are required [6,8]. These are time‐consuming, expensive, and may imply patient displacements.…”
Section: Introductionmentioning
confidence: 99%
“…2014 yılında yapılan başka bir çalışmada herhangi bir göz rahatsızlığı bulunmayan sağlıklı bireylerden ve akromatopsi ile doğuştan sabit gece körlüğü bulunan bireylerden alınan fERG sinyallerinin 'a' bileşenlerinin analizinde farklı sinyal işleme tekniklerinin (PCA, FA ve DA) başarımlarını karşılaştırmışlardır. Yöntemlerin içerisinde Meksika şapka dalgacığın kullanıldığı DA yönteminin diğer yöntemlere kıyasla daha başarılı olduğu tespit edilmiştir [19]. Mathieu Gauvin ve ark.…”
Section: Introductionunclassified